Ovarian Epithelial-Stromal Interactions: Role of Interleukins 1 and 6 - Kamisha T. Woolery; Patricia A. Kruk (Obstetrics and Gynecology International)
Ovarian epithelial cancer is the most lethal gynecologic malignancy. The high mortality is attributed to the fact that most cases typically present in late stage when ovarian cancer (OC) has already spread beyond the ovary. Ovarian epithelial cancer cells are shed into intraperitoneal ascites and easily disseminate throughout the peritoneal cavity with preferential metastasis to the omentum, peritoneum, and local organs. Understanding how ovarian epithelial cells interact with and modulate their microenvironment can provide insight into the molecular mechanism(s) involved with malignant transformation and progression which may eventually identify novel diagnostic, prognostic, and therapeutic targets. The objective of this paper is to provide a brief consideration of ovarian surface epithelial-stromal interactions in regard to normal physiological function and tumor progression as influenced by two potentially key interleukins, interleukins-1 (IL-1) and -6 (IL-6), present in the microenvironment. Lastly, we will consider the clinical implications of IL-1 and IL-6 for OC patients.